PENGEMBANGAN PEMBELAJARAN TEKNIK DIGITAL DENGAN MEDIA PERANGKAT LUNAK PROTEUS DAN EMULATOR JURUSAN TEKNIK INFORMATIKA UNIVERSITAS KANJURUHAN - Syaminan M.Kom (STMIK YADIKA BANGIL, 2020)
Abstract : Proteus professional is a group of electronic software used to assist designers in designing and simulating a circuit electronic. This software has two functions at the same time in one package, one package as a software for drawing automatic schematics and can be simulated which is named ISIS. The second package is used as a Printed Circuits Board (PCB) image which is named ARES. Directly, the conversion from schematic to PCB can be done in this Professional Proteus software. Prof. ISIS Prooteus has always friendly versions, starting from version 7.0 to 8. each version increase with the addition of library components that can be taken and used in drawing or designing . As an electronic frame designer, he first used ISIS as a medium that made it easier to play and simulate. The many libraries of the Proteus Profession onal ISIS make this software a complete simulation software, namely from active components, Analog, Trasistor, SCR, FET, types of buttons, types of switches / relays, digital IC, amplifier IC, programmable IC (microcontroller ) and IC memory. Apart from being supported by the completeness of components, it is also supported by the completeness of measuring instruments such as voltmeters, ampere meters, oscilloscopes, signal analyzers, and frequency generators. The completeness of the features provided is Proteus Professional ISIS is one of the electronic simulation software.Emulator writer is a text media service to help programs, especially by using digital number codes and can be collaborated with proteus, is a window form media designed by the author to make it easier for beginners who want to learn about microcontroller programming, can be used to write programming / coding with code Binary and Hexa numbers are made in Indonesian with the aim that beginners who are just starting to learn about digital-based programming if there are errors, instructions, or procedures, they will be shown in an Indonesian warning. Key words: digital simulation with software